VD_FINDINFO HC / 2019 / 193 vom 11. März 2018 - VD Tribunal cantonal (2018)
DÉCISION D'IRRECEVABILITÉ, CHOSE JUGÉE, DÉLAI DE RECOURS, RESTITUTION DU DÉLAI | 148 al. 1 CPC, 311 al. 1 CPC (CH), 59 al. 2 let. e CPC (CH)